The Platform Swithching Concept - orhun ekren; ahmet ozkomur (Cumhuriyet University, 2012)
The success of the dental implants mostly depends on the health of hard and soft tissues. One of the most important reason of dental implant failure is the crestal bone resorption around implants. It is generally accepted that marginal bone loss is about 1-1.5 mm in the first year after functional loading and 0.1 mm in subsequent years annually.              The resorption of the marginal bone effects the success of the dental implants in functional loading, aesthetics and if the resorption is accompanied with gingival recession it also effects the hygien control negatively.             Platform switching is a definition refers the reduction of the abutment diameter with respect to diameter of the dental implant. The concept rised by the use of 4 mm standart implant abutments over 5 mm and 6 mm implants. Long term follow up of these wide platform-small abutment combinations showed higher levels of bone preservation which encouraged the manufacturers to change their design in order to adapt this concept.             The aim of this review is to explain the logic and the principles of the platform switching concept.